Pengaruh Terapi Suportif: Kelompok terhadap Perubahan Harga Diri Klien TB Paru di Kecamatan Umbulsari Kabupaten Jember (The Influence of Group Supportive Therapy for Change of Self-Esteem Client Pulmonary TB in the District Umbulsari Jember) - Bafidz Arifahmi Bachtiyar; Erti Ikhtiarini Dewi; Latifa Aini Susumaningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Long treatment and environments that do not provide support for clients with pulmonary tuberculosis tend to create in impaired self-esteem. One solution to overcome the problems of self-esteem in clients with pulmonary TB is supportive therapy. The effect of group supportive therapy for change of self-esteem in the District Umbulsari Jember . This study is a quasi-experimental study with control group design with 18 samples obtained through total sampling method. Results of independent t - test states that supportive therapy group had an influence on changes in pulmonary TB esteem clients are between the intervention group and the control group may know the value of t = 8.53 with p value 0.000 < 0.05, which means that there are differences in self-esteem client pulmonary tuberculosis significantly between the intervention group and the control group.So , it can be concluded that the interference of low self esteem in clients pulmonary TB can be treated with group supportive therapy. Keywords: support group therapy, self esteem, tuberculosis